In vitro antibiofilm evaluation of ocimum basilicum extracts against enterococcus faecalis - Yulina, Vera; Herdiyati, Yetty; Chemiawan, Eka (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Enterococcus faecalis is the main pathogenic bacterium in the root canal which is resistant to various antibacterial agents. Recently, the discovery of a new antibacterial agent research focus in herbal dentistry, one of which is basil leaves. Basil (kemangi) leaves (Ocimum basilicum) are herbs that have various active components as anti-biofilm agents. This study aims to evaluate the effectiveness of antibacterial potential of O. basilicum extract against the biofilm formation by E. faecalis. This research uses true experimental laboratory design. The kemangi leaves were gradually extracted with various polarity based organic solvents (n-hexane and ethyl acetate). The evaluation of the anti-biofilm activity of the extracts against E. faecalis aimed to determine the minimum biofilm inhibitory concentration (MBIC) and minimum biofilm eradication concentration (MBEC) values. Calcium hydroxide paste (calcipex) was used as a positive control. The assay data were analyzed using an independent paired T-test. Ethyl acetate, n-hexane extract of O. basilicum, and calcipex inhibited biofilm formation by E. faecalis with MBIC values of 100%, 100%, and 75.20% at the concentrations of 2.5%, 10%, and 3.13%, respectively. The MBEC values were 100%, 100%, and 71.01% at the concentrations of 5%, 2.5%, and 3.13%, respectively. The statistical analysis by ANOVA test on MBIC and MBEC showed significant differences with p-values < 0.05. Further statistical valuation with post hoc analysis showed highly significant differences with p-values < 0.01. This study has found that O. basilicum leaves extracts have the capacity and ability to inhibit and eradicate E. faecalis biofilms.